Determination of factors of maximum influence on the occurrence of fires in conditions of limited a priori information in the war zone in the east of Ukraine - Olga Butenko; Anna Topchiy (Geo&Bio, 2023)
The expediency of using the inverted Floyd–Warshall algorithm for a deeper study of factors of maximum influence on the occurrence and development of fires in the war zones of Donetsk and Lugansk oblasts is shown. It relates to the fact that fire is one of the important parameters of the monitoring system that affects the ecological situation in the region. However, in the absence of a priori information about fires and hostilities, the formation of a set of factors influencing the occurrence and development of fires in the region is a laborious process. The primary assessment of a priori information allows generalising and averaging the factors that influence the occurrence of fires in these regions. The inverted Floyd–Warshall algorithm is a simple algorithm to implement, although to eliminate errors in mathematical calculations and to form adjacency matrices, a program code was developed in the Python programming language. Using the built-in visualisation software tools, a weighted oriented graph of factors influencing fires was built; the weights of these factors, determined at the initial stage, are also indicated on the edges of the graph. An adjacency matrix has been compiled, which contains information about the presence or absence of links between graph vertices. The factors of maximum influence on the occurrence and development of fires in Donetsk and Lugansk oblasts are determined, considering the specifics of the area and the results of hostilities. The results of the algorithm confirmed that hostilities create a fire hazard situation in the region. Due to the lack of a complete set of data, it becomes almost impossible to obtain results of mathematical calculations that are more accurate, since open-source data cannot provide errorless data on hostilities. For the same reason, the study area is not divided into separate segments in order to obtain more accurate results of mathematical calculations for each segment. Despite this, the software implementation of the inverted Floyd–Warshall algorithm is a universal method for solving the problem of finding and selecting factors of maximum and minimum influence on the occurrence of fires in environmental monitoring issues.